Artemis inhibition as a therapeutic strategy for acute lymphoblastic leukemia - Ogana, Heather A.; Hurwitz, Samantha; Hsieh, Chih-Lin; Geng, Huimin; Müschen, Markus; Bhojwani, Deepa; Wolf, Mark A.; Larocque, James; Lieber, Michael R.; Kim, Yong Mi (Frontiers in Cell and Developmental Biology, 2023)
As effective therapies for relapse and refractory B-cell acute lymphoblastic leukemia (B-ALL) remain problematic, novel therapeutic strategies are needed. Artemis is a key endonuclease in V(D)J recombination and nonhomologous end joining (NHEJ) of DNA double-strand break (DSB) repair. Inhibition of Artemis would cause chromosome breaks during maturation of RAG-expressing T- and B-cells. Though this would block generation of new B- and T-cells temporarily, it could be oncologically beneficial for reducing the proliferation of B-ALL and T-ALL cells by causing chromosome breaks in these RAG-expressing tumor cells. Currently, pharmacological inhibition is not available for Artemis. According to gene expression analyses from 207 children with high-risk pre-B acute lymphoblastic leukemias high Artemis expression is correlated with poor outcome. Therefore, we evaluated four compounds (827171, 827032, 826941, and 825226), previously generated from a large Artemis targeted drug screen. A biochemical assay using a purified Artemis:DNA-PKcs complex shows that the Artemis inhibitors 827171, 827032, 826941, 825226 have nanomolar IC50 values for Artemis inhibition. We compared these 4 compounds to a DNA-PK inhibitor (AZD7648) in three patient-derived B-ALL cell lines (LAX56, BLQ5 and LAX7R) and in two mature B-cell lines (3301015 and 5680001) as controls. We found that pharmacological Artemis inhibition substantially decreases proliferation of B-ALL cell lines while normal mature B-cell lines are not markedly affected. Inhibition of DNA-PKcs (which regulates Artemis) using the DNA-PK inhibitor AZD7648 had minor effects on these same primary patient-derived ALL lines, indicating that inhibition of V(D)J hairpin opening requires direct inhibition of Artemis, rather than indirect suppression of the kinase that regulates Artemis. Our data provides a basis for further evaluation of pharmacological Artemis inhibition of proliferation of B- and T-ALL.